Vínculo mãe-filho(a) de crianças expostas e não expostas à Violência entre Parceiros Íntimos: um estudo de caso múltiplo - Zafalon, Julia Floriano (Universidade Federal de São Carlos, 2021)
Healthy family experiences contribute to the development of adaptative child behaviors; adverse experiences, such as exposure to intimate partner violence (IPV), are associated with short- and long-term problems. The present study aimed to develop a multiple case study comparing dyads exposed and not exposed to IPV in relation to the mother-child bond. Five mothers (30-46 years) and 5 children, 3 girls and 2 boys, aged between 9 and 11 years (M=9.8; SD=0.84) participated in the study. Mothers answered the Revised Conflict Tactics Scale (CTS2-R) and children answered the Exposure to Domestic Violence Scale (EEVD), the Attachment to Parents Assessment Scale and a semi-structured interview. The data indicated that four mothers reported a history of physical IPV, two of which were in a shelter situation with their children at the time of collection. It was found that the children of women victims of physical IPV were exposed to a greater number of risk factors and had lower values on the scale of attachment to parents when compared to the other children. Future studies to investigate the relationship between these variables, supporting future interventions for children exposed to violence, is discussed.
Mother-child bonding of children exposed and not exposed to Intimate Partner Violence: a multiple case study
Keywords: Violência entre parceiros íntimos; Criança; Vínculo; Estudo de caso; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA